Public Intellectuals and Politics in Cuba: A Case Study of Cosme de la Torriente y Peraza (1872–1956). (1st December 2015) - Jorge Renato Ibarra Guitart; Gastón A. Fernández
Abstract : The dependent character of the Cuban bourgeoisie in the aftermath of the Revolution of 1895–98, the cycles of economic and political crisis with roots in the Island's sugar monoculture and economic dependency on the US and the pattern of US interventions in Cuban affairs under the Platt Amendment produced a profound crisis of legitimacy of the Cuban state during the Republic. Public intellectuals, in Antonio Gramsci's definition, played an important role in mediating the cyclical crisis with the purpose of maintaining public consent for Republican institutions, political parties and elites. Cosme de la Torriente y Peraza was a leading figure among public intellectuals who performed this role on behalf of Republican democracy beginning with the administration of President Estrada y Palma (1902–06) and culminating with the Fulgencio Batista regime (1952–58). His political career provides insights into the root causes of the crisis of confidence in Republican political institutions and leaders that paved the way for the Revolution of 1958.